Дослідження гострої токсичності натрій 2-(4-метил-5-(тіофен-2-іл)-4-H-1,2,4-тріазол-3-ілтіо)ацетату, що проявляє актопротекторну дію - Пругло, Євген Сергійович; Саліонов, Володимир Олександрович; Панасенко, Олександр Іванович; Книш, Євгеній Григорович; Пругло, Е. С.; Салионов, В. А.; Панасенко, А. И.; Кныш, Е. Г.; Pruglo, Ye. S.; Salіonov, V. O.; Panasenko, O. I.; Knysh, Ye. G. (My University, 2015)
Цель работы — исследование токсических свойств натрий 2-(4-метил-5-(тиофен-2-ил)-4-Н-1,2,4- триазол-3-илтио)ацетата, который имеет высокие показатели актопротекторного действия. Оценка острой токсичности проведена на беспородных белых крысах массой 180–240 г, которым натощак однократно внутрибрюшинно вводили натрий 2-(4-метил-5-(тиофен-2-ил)-4-Н- 1,2,4-триазол-3-илтио)ацетат. При исследовании острой токсичности каждую дозу испытывали на двух и шести животных. Период последующего наблюдения составил 14 сут., в течение которых фиксировали характер и продолжительность симптомов интоксикации, сроки гибели и количество погибших животных от каждой введенной дозы. На основании полученных экспериментальных и расчетных данных токсикометрии можно сделать вывод, что в плане возникновения и развития острых отравлений натрий 2-(4-метил-5-(тиофен-2-ил)-4-Н-1,2,4-триазол-3-илтио)ацетат при его однократном внутрибрюшинном (внутривенном) введении токсикологически является относительно безопасным для теплокровных животных, в том числе и для человека. Among the requirements to drugs great importance represent their efficiency and low rates of toxicity. The aim of the work was the research of toxic properties of sodium 2-(4-methyl-5-(thiophene-2-yl)-4- H-1,2,4-triazoles-3-ilthio)acetate, which shows high indicators of the actoprotective action. Methodological basis of the toxicological experiments realization were based on the requirements, proposed in the recommendations of clinical drug’s research. Basic methodical techniques of toxicological experiments were performed on the basis of works of V. B. Prozorovskyi and M. L. Belenkyi. The assessment of acute toxicity was conducted on outbred white rats weighing 180-240 g, which were once injected intraperitoneally with sodium 2-(4-methyl-5-(thiophene-2-yl)-4-H-1,2,4-triazol-3- ilthio)acetate. Rats were obtained from nursery of the Institute of Pharmacology and Toxicology of Ukraine. The animals were kept on a standard diet with natural light regime “day-night”. Researches were performed on the basis of “Rules of preclinical safety evaluation of pharmacological agents (GLP)”. During the research of the acute toxicity each dose was tested on 2 and on 6 animals. The following term was 14 days, during which we take into account the nature and the duration of intoxication symptoms, the death terms and the number of dead animals from each administered dose. Based on the experimental and calculated facts of the toxycometry, can be concluded that sodium 2-(4-methyl-5-(thiophene-2-yl)-4-H-1,2,4-triazoles-3-ilthio)acetate with its single intraperitoneal injection is relatively harmless and practically safe in toxicological respect to warm-blooded animals and to humans in terms of the emergence and development of acute poisoning.
Исследование острой токсичности натрий 2-(4-метил-5-(тиофен-2-ил)-4-н-1,2,4-триазол-3-илтио)ацетата, который проявляет актопротекторное действие
The research of an acute toxicity of sodium 2-(4-methyl-5-(2-tіofen-2-іl)-4-h-1,2,4-trіazol-3-іlthіo)acetate, that shows the actoprotective effect
Keywords: острая токсичность; внутрибрюшинное введение; 1,2,4-триазол; acute toxicity; intraperitoneally; 1,2,4-triazol